Breakage of stylet inside endotracheal tube following intubation (Journal of Patan Academy of Health Sciences, 2018)
A 52-year-old lady was scheduled for hemithyroidectomy for right colloid goitre. After the preanesthetic check-up, she was classified as an American society of anesthesiologists (ASA) physical status I. Her baseline vitals parameters were within normal limits. After receiving premedication, she was induced and intubated with a 7.0 mm ID flexometallic endotracheal tube (ETT) preloaded with a malleable aluminium stylet. Shortly afterwards, while fixing the ETT, the size of the stylet was noticed to be shorter than initial length. Immediately, ETT was removed and replaced with a new one. The broken piece of stylet was found inside the removed ETT.